2004
DOI: 10.1097/01.mcg.0000123164.86324.24
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Symptom Behavior in Patients With Persistent Dyspepsia During Treatment

Abstract: In the majority of dyspeptic patients, symptoms change continuously as time goes on. Symptom instability is not influenced by diagnostic procedures or therapy. Thus, there is little sense in symptom-based management of dyspepsia in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In the present study, an average of 5.2 symptoms were seen in patients with reflux esophagitis, of which reflux type symptoms occurred most frequently; however, dysmotility type symptoms and ulcer type symptoms were also observed in about 40-50% of patients. Similar numbers (5.4 on average) were reported from other studies in patients with upper abdominal symptoms possibly associated with acid [13,14]. A recent study reported that more than 50% of patients with FD had at least five symptoms [15].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, an average of 5.2 symptoms were seen in patients with reflux esophagitis, of which reflux type symptoms occurred most frequently; however, dysmotility type symptoms and ulcer type symptoms were also observed in about 40-50% of patients. Similar numbers (5.4 on average) were reported from other studies in patients with upper abdominal symptoms possibly associated with acid [13,14]. A recent study reported that more than 50% of patients with FD had at least five symptoms [15].…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, it remains unknown how to identify subgroups of patients for whom a specific treatment modality is most suitable. The previous Rome II subdivision of functional dyspepsia had limited clinical impact because the subgrouping was unstable over a short period of time, and it was difficult to ascertain the ''predominant'' symptom as well as the meaning of ''discomfort'' [9,32]. It has been hoped that the Rome III subclassification would distinguish patients with distinct pathophysiological mechanisms and thus permit more specific management in each subgroup [1].…”
Section: Discussionmentioning
confidence: 98%
“…5 However, subsequent research has shown that identifi cation of the predominant symptom lacks stability over a short time period. 8,9 Nevertheless, there is increasing evidence of heterogeneity of FD based on factor analyses in the general population and in referral populations ( Table 2). These analyses have failed to support the existence Epigastric refers to the region between the umbilicus and lower end of the sternum, marked by the midclavicular lines.…”
Section: Rationale For New Subclasses Of Functional Dyspepsiamentioning
confidence: 98%